(untitled) (Mutah Journal of Humanities and Social Sciences (MJHSS), 2025)
This study aimed to investigate the relationship between advertising and profitability in the Jordanian manufacturing sector for the period (2011-2020), at the level of (22) sub-sectors, relying on the method of analyzing time series and cross-sectional data (Dynamic Panel data). The study employed several methodologies to confirm the credibility of the results, including Generalized Method of Moments (GMM). To confirm the validity of the results, standard models that capture the relationship between advertising intensity and profitability were estimated using the Fully Modified Ordinary Least Square (FMOLS) methodology, the Fixed Effects (FE) methodology, and the Random Effects (RE) methodology. The study found a reciprocal relationship between advertising and profitability in the Jordanian manufacturing sector, where the results showed that the direction of the effect was as follows: a significant and positive effect of advertising intensity on profitability, as well as a significant and positive effect of profitability on advertising. The results of the study also indicated that there is a significant and positive effect of concentration on advertising and profitability. Also of the important results that the study reached is that the effect of advertising on profitability is a function of concentration, which confirms that the structure-conduct-performance hypothesis applies to the Jordanian manufacturing sector.